Case report: Carbohydrate malabsorption in inpatients with anorexia nervosa - Buck, Patrizia; Goebel-Stengel, Miriam; Mack, Isabelle; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2022)
Background Gastrointestinal (GI) complaints are frequently observed in patients who suffer from anorexia nervosa (AN). These symptoms may hamper treatment and weight regain and are often perceived as the cause, not the consequence, of the disease. Since carbohydrate malabsorption also produces these symptoms, this might underly or contribute to these complaints. So far, the role of carbohydrate malabsorption (fructose malabsorption and lactose intolerance) in AN has not yet been investigated. Methods For this case series, inpatients with AN of restrictive type (n = 3), purging type (n = 3), and atypical AN (n = 1) conducted hydrogen breath tests with 25 g of fructose and 50 g of lactose to investigate carbohydrate malabsorption. Results were then analyzed in association with body mass index (BMI) and patient-reported outcomes (disordered eating, body image disturbances, anxiety, depressive symptoms, perceived stress, and GI complaints). Results Based on the hydrogen breath test results, three of the seven female patients were classified as lactose intolerant and one presented fructose malabsorption. Both hydrogen curves for fructose (r = –0.632, p < 0.001) and lactose (r = –0.704, p < 0.001) showed a negative correlation with BMI. No association was observed between hydrogen values and patient-reported outcomes. Conclusion In patients with AN, GI symptoms caused by intolerance of common monosaccharides and disaccharides may be an underestimated burden and should be considered in the diagnosis and therapy of patients with AN. Due to the observed correlation with BMI, GI complaints after ingestion of fructose or lactose likely develop with decreasing body weight and are potentially reversible with weight regain.